Factors influencing online shopping spending among UUM students - Nur Harisa, Aniruddin (2018)
Online shopping is growing rapidly in Malaysia as a new way to shop due to the advancement of the internet. The convenience of online shopping rendering it an emerging trend among consumers, especially the young generation. Therefore, the purpose of this research is to identify the factors that influence online shopping spending among students in University Utara Malaysia. The specific objectives in this research include to identify how consumer socioeconomic characteristics and characteristics of the web as a sale channel such as security and time saving influence online shopping spending among UUM students. It also examined the influence of website characteristics towards online shopping spending. Primary data collection method in the form of self-administrated questionnaire and multistage sampling technique was used to collect the data. University students that currently pursuing their studies in University Utara Malaysia were selected as the subject of analysis. 304 out of 400 sets of questionnaires distributed were valid for analysed using SPSS version 22. Independent sample t-test, Pearson's correlation analysis and multiple regression analysis were used to test hypotheses and detennine the significance and degree of relationship between dependent and independent variables. The results and findings show that in terms of gender, female make online purchased more than male and in terms of age, higher age group make more online purchased compared to lower age group. For the allowance, respondents who have higher allowance spend more on online shopping compared to respondents who have lower allowance. Moreover for security, time saving and website design variables, there was found to be significant and positive relationship with consumer spending. Security is the most relatively powerful independent variable in influencing consumer spending towards online shopping. The study recommended that various risk reducing strategies should be developed by online retailers because consumers are more likely to make online purchases if they feel their security and privacy provided by online vendors are adequate. Another recommendation is that further research could examine variant groups of online consumers in other contexts, for example sample from working adults were to be included to minimise sampling bias.